2021
DOI: 10.1088/1742-6596/1796/1/012119
|View full text |Cite
|
Sign up to set email alerts
|

Students’ mathematical communication skills through vlog in project-based learning based on the unity of sciences

Abstract: This study aims to determine the increase in mathematical communication skills of students of UIN Walisongo Semarang using mathematics teaching materials that apply Project Based Learning through vlogs based on unity of sciences. The importance of mathematical communication skills can help students more easily communicate the results of their mind on mathematical problems through symbols, diagrams, tables, or the other media. Mathematical communication skills make it easier for students as prospective teachers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…; Secules et al, 1992). Similarly, among the 60 studies including this literature review, there were only two studies on teaching science and one study on mathematics (Arrieta et al, 2020; Firdiani et al, 2020; Fitriani & Rohman, 2021). Even though the studies’ findings reported a positive impact on students learning, it’s difficult to generalize these findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Secules et al, 1992). Similarly, among the 60 studies including this literature review, there were only two studies on teaching science and one study on mathematics (Arrieta et al, 2020; Firdiani et al, 2020; Fitriani & Rohman, 2021). Even though the studies’ findings reported a positive impact on students learning, it’s difficult to generalize these findings.…”
Section: Discussionmentioning
confidence: 99%
“…No studies discussed the other language elements, such as grammar, though research has been done on using instructional videos for teaching grammar (Alharbi, 2019;Haight et al, 2007;Herron et al, 2006;_ Ilin et al, 2013;Mohammed, 2013.;Secules et al, 1992). Similarly, among the 60 studies including this literature review, there were only two studies on teaching science and one study on mathematics (Arrieta et al, 2020;Firdiani et al, 2020;Fitriani & Rohman, 2021). Even though the studies' findings reported a positive impact on students learning, it's difficult to generalize these findings.…”
Section: Vlogging In K-12 Educationmentioning
confidence: 94%
“…Consequently, to respond to the statements mentioned above by the authors and the orders provided by the Department of Education (DepEd) in the Philippines, the researcher had conducted this classroom action research (Kunasaraphan, 2018) to his instructions, and project VLOGI was his intervention. This assertion was supported by (Fitriani & Rohman, 2021), who claimed that instructional vlogs created and posted to YouTube through a project-based learning model were effective and feasible learning modalities in distance education, increasing mathematical communication skills. The researcher's intervention, named project VLOGI, was inspired by video blogging (Vlog), the new blogging trend for digital natives in contemporary times (Gao et al, 2010).…”
Section: Introductionmentioning
confidence: 92%
“…Nonetheless, whatever situations and hindrances to learning that learners may encounter, the government and the department of education have always had solutions to have sustainability in education with the help of the teachers. As a result, the researcher's options in mind was this project VLOGI which would be attractive to learners since it is currently the trend among digital natives through these vlogs (Fitriani & Rohman, 2021). Similarly, due to the pandemic, it is also very timely and relevant to be utilized as (SIM) as Vlogs in the asynchronous or synchronous platform of teaching (Rigo & Mikus, 2021).…”
Section: Introductionmentioning
confidence: 99%